Why Don't Labor and Capital Flow Between Young and Old Countries? - Philipp an de Meulen; Lena Calahorrano (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
To counter the effects of population aging in rich industrialized countries, raising immigration from and raising capital exports to younger developing countries are often seen as alternative solutions. In this paper, we explicitly account for mobility constraints in the form of immigration restrictions in industrialized countries and expropriation risk in developing countries to investigate whether efficiency gains from factor movements are likely to be realized. We set up a one-period general equilibrium model of two economies with young and old individuals. Emigration from the developing country weakens its young generation's expropriation preferences, permitting more FDI. However, if the bulk of capital is invested abroad, the old investor's utility gain from immigration is low. Our model suggests that large differences in age structures do not unambiguously encourage large factor flows, when the level of factor flows is determined by policy.
Keywords: D78; F21; F22; J10; 330; Demographic Change; Political Economy; Immigration Policy; International Investment